Pelvic malignant mesenchymoma. A case report - Pedro León-Acosta; Pedro Rosales-Torres; Rafael Pila-Pérez (Revista Información Científica, 2023)
It was reported a case of a 73 years old patient with a history of an unknown outcomes surgical procedure 5 years ago at the Hospital Clínico Quirúrgico Docente “Amalia Simoni” in Camaguey, Cuba. He presented pain and functional limitation of the right lower limb, which led to the resection of a tumor in the ipsilateral femur; five years later the tumour present signs of recurrence, this time with invasion of the bony pelvis and rectum and resulting in urinary disorders and constipation. Pelvis bone radiology, computed tomography scan and magnetic resonance imaging of the pelvis showed a mixed tumor with lytic lesions that invaded and displaced the organs in the pelvic cavity. The patient underwent excision of the tumor, which was 173×156 mm, weighing approximately 1.380 g. Histopathological analysis of the surgical resection specimen revealed a pelvic malignant mesenchymoma.